Airway stenting in a child with spondyloepiphyseal dysplasia congenita: 13-Year survival. (August 2017) - Nenna, Raffaella; Midulla, Fabio; Masi, Laura; Bacci, Giacomo Maria; Frassanito, Antonella; Baggi, Roberto; Brandi, Maria Luisa; Avenali, Stefano; Mirabile, Lorenzo; Serio, Paola
Abstract: We describe the case of a boy with spondyloepiphyseal dysplasia congenita. At birth, he experienced severe respiratory distress necessitating tracheotomy. Endoscopy done because mechanical ventilation failed to resolve desaturations disclosed severe tracheo-bronchomalacia. A Polyflex silicone stent was placed in the trachea (replaced by Y-Dumon stent) and 2 Palmaz metallic stents in the mainstem bronchi (overlapped with 2 Jomed stents 5 years later). Airway stenting guaranteed a suitable respiratory status and allowed a child who was expected to die at birth, to reach 13.5 years old in good conditions.